Penggunaan Media Visual Nilai - Nilai Pancasila dalam Pembelajaran PPKN - Qiromah, Muflihatul Qiromah (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
This research is motivated by the lack of public understanding of the values of pancasila.this study uses visual media toimprove learning achievement of pancasila values andattitudes that contain pancasilavalues andmake learning more fun.Type of research used is field research.Data collection by observation and interview.Data were analyzed using qualitative analysis.Visual media research results in the from of pancasila values in the from of Pancasilasymbols and pictures of Pancasilavalues using demonstration methods matchthe value of Pancasila with Pancasila symbols in group showing visualization media pancasila value are more effectiveto make learning more fun and visual media pancasila values are more effectivein increasing student motivation in learning that contains pancasila values.